Problem based learning to increase competence of critical thinking and problem solving - Tri Murhanjati Sholihah; Badraningsih Lastariwati (Journal of Education and Learning (EduLearn), 2020)
Critical thinking and problem solving is one of the competencies that must be possessed to meet the 21st Century. This competence is very important to be mastered by students, especially vocational high school students. One learning model that can hone 21st Century competencies is Problem Based Learning. This research was carried out on productive subjects of the Trial. This study aims to determine the improvement of critical thinking and problem solving competencies, and student learning outcomes on subject matter subjects. This study uses a classroom action research design with measurement of competence using observation and measurement of learning outcomes using a multiple choice written test. The results of the study showed an increase in thinking and problem solving critical competencies from the first cycle of 37.4% to the second cycle of 78.2%. While the average value of the first cycle is 70.4 and the second cycle is 86.4. Students who reach KKM in cycle I are 38% and in cycle II 82%.